Comparison between Full Endoscopic Lumbar Discectomy (FELD) and Micro Discectomy (MD) in Patients with Lumber Disc Herniation in Terms of Pain Relief and Functional Outcome - Inam, Shahzad; Talha, Muhammad; Shamim, Babar; Qasmi, Shahzad Ahmed; Ali, Sajid; Awan, Liaqat Mahmood (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare pain control and functional outcome in fully endoscopic lumbar discectomies verses open discectomies in local population.Study Design: Quasi-experimental studyPlace and Duration of Study: Department of Spine Surgery, Combined Military Hospital Rawalpindi, Pakistan from October 2023 to March 2024Methodology: Study included 200 patients divided into two groups of 100 each; Group-A endo discectomy group and Group-B open discectomy group. In Group-A patients underwent endoscopic lumbar discectomy (both transforaminal and inter laminar) while in Group-B open micro discectomy was performed. Pain relief in the patients was assessed using Numerical Rating Scale (NRS) and OSWESTRY Disability Index (ODI) at immediately post-op, at the time of discharge and at 6 weeks post-op follow-up. Functional outcome was assessed in terms of patient satisfaction at 6 week post-op follow-up.Results: There were 140(70%) male and 60(30%) females. The mean age was 37.61±9.57 and 38.59±9.71 years in Group-A and B respectively. Intergroup comparison yields significant difference (p